Distribution and Diversity Inventory of Bird Species in the Campus Area of Universitas Sulawesi Barat and Its Surroundings - Putera, Alexander Kurniawan Sariyanto; Isdaryanti (Center for Ecology, Conservation and Ethnobiology Studies, Universitas Sulawesi Barat, 2024)
This study elucidates the diversity of birds at the campus of Universitas Sulawesi Barat, a region that is part of the Wallacea ecosystem, which is renowned for its high biodiversity. The research involved an inventory of 22 bird species belonging to 17 families, with a total of 180 individuals recorded. Among the observed species, seven were distributed across various habitat types, while 13 others were found in habitats less influenced by human activities, such as grasslands, shrubs, and trees. Interestingly, two species, Perkutut Jawa and Kacamata Sulawesi, were exclusively found in habitats frequently affected by human activities, such as settlements and plantations. The study also revealed that approximately 27.27% of the 22 recorded bird species are Sulawesi endemic species, while 72.73% are non-endemic species. These findings provide important insights into the composition and distribution of birds in the study area and have significant implications for conservation efforts. Protecting natural habitats, especially those supporting endemic species, should be a priority. In addition, a better understanding of how birds interact with human-modified habitats is necessary to develop effective conservation strategies. Further studies on specific species may also be required in environments that are increasingly fragmented by human activities. Advancing knowledge in ornithology is essential for preserving bird diversity in the Wallacea region.